2015
DOI: 10.1186/s40463-015-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4-related diseases in the head and neck: A systematic review

Abstract: BackgroundImmunoglobulin G4 related disease (IgG4-RD) is a poorly understood chronic inflammatory disorder affecting the middle-aged and elderly that can present to the otolaryngologist. We aim to summarize the current literature regarding the manifestations and management of IgG4-RD in the head and neck.MethodsPubmed and EMBASE were searched using the term relevant search algorithm utilizing keywords such as: IgG4 related disease, head and neck, orbit, salivary glands, sialadenitis, Kuttner, angiocentric eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(115 citation statements)
references
References 57 publications
2
104
0
9
Order By: Relevance
“…However, in contrast to the female preponderance of autoimmune (Hashimoto's) thyroiditis, there is no sex predilection for IgG4RTD. It is believed to occur equally among males and females [1,2]. Recent reports have also suggested that a small fraction of Graves' disease patients also have elevated IgG4 levels with some features suggestive of IgG4TD [21,22].…”
Section: Igg4 Related Thyroid Disease (Igg4rtd)mentioning
confidence: 99%
See 4 more Smart Citations
“…However, in contrast to the female preponderance of autoimmune (Hashimoto's) thyroiditis, there is no sex predilection for IgG4RTD. It is believed to occur equally among males and females [1,2]. Recent reports have also suggested that a small fraction of Graves' disease patients also have elevated IgG4 levels with some features suggestive of IgG4TD [21,22].…”
Section: Igg4 Related Thyroid Disease (Igg4rtd)mentioning
confidence: 99%
“…IgG4-related disease per se as an entity was recognised only in 2001, with autoimmune pancreatitis being the prototype organ involvement [1]. Thyroid involvement in IgG4RD is rare, believed to occur in < 4% of cases [1,2]. However, it is likely that the diagnosis is grossly under reported due …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations